A clinical trial of ropivacaine in arthocentesis for TMD - Laifeng Huang; Zeliu Huang; Shiyun Bi; Huaming Mai (BMC, 2024)
Abstract Introduction This study aims to compare the efficacy of ropivacaine and lidocaine in the treatment of temporomandibular joint (TMJ) disorders, with the goal of exploring a more effective treatment for TMJ disorders. Methods Patients with Wilkes stage III and IV unilateral TMJ disorders were enrolled in the study. 0.5% ropivacaine was used for local anesthesia in group A, 2% lidocaine was used in group B. Sodium hyaluronate was injected after supra-articular lavage in both groups. The patients' general conditions, pain scores, and maximum opening before and after treatment were collected, the time of onset and maintenance of anesthesia, and the levels of inflammatory factors IL-1β and IL-6 in the joint lavage fluid were detected. Results Study showed that the onset of anesthesia was faster and longer maintained in group A. The decrease in IL-1β was more pronounced in group A (16.08 ± 3.10) than in group B (18.03 ± 2.84), p < 0.05. At 2 months after treatment, the joint clicking rate was higher in group A (75%) compared to group B (35%), p < 0.05. At 3 months after treatment, the joint clicking rate was higher in group A (76.69%) compared to group B (40%) and the maximum mouth opening was greater in group A (45.00 ± 2.38) compared to group B (41.73 ± 4.18), p < 0.05. There were no statistically significant differences in VAS score and lateral excursion in group A compared with group B at 2 months and 3 months after treatment. Conclusions Compared with lidocaine, the application of ropivacaine combined with sodium hyaluronate supra-articular lavage for the treatment of temporomandibular joint disorder is more clinically effective. Clinical trials Registration Number ChiCTR2300075241 (30/08/2023).